Transforming Pedagogies: Integrating 21st Century Skills And Web 2.0 Technology - Tucker, Shelia Y. (My University, 2014)
According to (P21), Partnership for 21st Century Skills (n.d.), unless the gap is bridged between how students learn and how they live, today’s education system will face irrelevance. The way people work and live has been transformed by demographic, economic, political, technological, and informational forces. Schools must adapt to these changing conditions in order to thrive. Students must be equipped to live in a multifaceted, multitasking, technology-driven world. And, regardless of their economic background, we must also ensure that all students have equal access to this new technological world. Collaborative learning theory which is connected to constructivism pedagogy requires students to work together to solve problems. Students need lifelong learning skills i.e., communication and information skills, problem-solving and thinking skills, and interpersonal and self-directional skills. The challenge becomes to deliberately incorporate learning skills into classrooms strategically and broadly. In this digital age, students must learn to use tools essential to everyday life and workplace productivity. They live in a world of almost unlimited streams of profound information, difficult choices and enormous opportunity. Teachers can create a 21st century context for learning by taking students out into the world, by bringing the world into the classroom, and by creating opportunities for students to collaboratively interact with each other (Learning for the, n.d.). One way of accomplishing this task is by employing the use of the Internet to connect Web 2.0 technology and 21st century skills. These skills are essential due to increased global competition, rising workforce capabilities, and accelerated technological change (Learning for the, n.d.).